Predictive value of intraoperative flat CT for intracranial hemorrhage after mechanical thrombectomy in acute anterior circulation large vessel occlusion - ZHOU Xing⁃chen; YANG Guang; ZHAO Biao; WANG Da⁃wei,; ZHANG Hui; MIN Jing⁃liang (Chinese Journal of Contemporary Neurology and Neurosurgery)
Objective To explore the predictive value of intraoperative flat CT scan for intracranial hemorrhage after mechanical thrombectomy in patients with acute anterior circulation large vessel occlusion (AAC⁃LVO). Methods A total of 106 patients with AAC⁃LVO who underwent mechanical thrombectomy at The Second Affiliated Hospital of Bengbu Medical University was conducted from March 2020 to June 2023. Intraoperative flat CT scan was performed among above patients to record CT values, high⁃density sign and mass effect. According to whether occurred intracranial hemorrhage after surgery, those patients were divided into intracranial hemorrhage group (n = 29) and non⁃intracranial hemorrhage group (n = 77). Univariate and multivariate stepwise Logistic regression analyses were used to screen the influencing factors of intracranial hemorrhage after mechanical thrombectomy. Receiver operating characteristic (ROC) curve was drawn to evaluate the predictive efficacy of intraoperative flat CT scan for postoperative intracranial hemorrhage. Results Logistic regression analysis showed that hypertension was a protective factor for (OR = 0.340, 95%CI: 0.123-0.941; P = 0.038). A high National Institutes of Health Stroke (NIHSS) score at admission (OR = 1.068, 95%CI: 1.010-1.129; P = 0.021), as well as intraoperative flat CT high⁃density sign (OR = 9.942, 95%CI: 2.631-37.567; P = 0.001), mass effect (OR = 23.564, 95%CI: 7.266-79.421; P = 0.000), and CT value ≥ 90 HU (OR = 9.714, 95%CI: 1.982-47.605; P = 0.005) were risk factors for postoperative intracranial hemorrhage. The ROC curve showed that the area under the curve (AUC) for intraoperative flat CT value ≥ 90 HU, mass effect and their combined prediction of postoperative intracranial hemorrhage were 0.82 (95%CI: 0.734-0.889, P = 0.000), 0.75 (95%CI: 0.661-0.833, P = 0.000) and 0.76 (95%CI: 0.668-0.838, P = 0.000), with sensitivity were 75.86%, 58.62% and 58.62%, and specificity were 88.31%, 92.21% and 93.51%. The predictive efficiency was highest for CT value ≥ 90 HU (t = 48.777, P = 0.000; t = 43.681,P = 0.000). Conclusions In patients with AAC⁃LVO undergoing mechanical thrombectomy, intraoperative flat CT high⁃density sign such as CT value ≥ 90 HU and mass effect can predict postoperative intracranial hemorrhage, and the predictive value of CT value ≥ 90 HU is relatively high.